A comprehensive review on the use of conductive materials to improve anaerobic digestion: Focusing on landfill leachate treatment. (1st May 2022) - Nabi, Mohammad; Liang, Hong; Cheng, Lang; Yang, Wenbo; Gao, Dawen
Abstract: Globally, around 70% of waste is disposed of in open dumps or landfill sites, with the leachate generated from these sites containing high concentrations of organic and inorganic compounds, which will adversely affect aquatic environments if discharged without proper treatment. Anaerobic digestion of landfill leachate is an environmentally-friendly method that efficiently converts organic compounds into methane-rich biogas. However, the widespread application of anaerobic digestion has been hindered by poor system stability, low methanogenic activity and a high level of volatile fatty acids (VFAs) accumulation, increasing the operational costs of treatment. Conductive materials can be added to the digester to improve the performance of anaerobic digestion in landfill leachate treatment systems and studies reporting the use of conductive materials for this purpose are hereby thoroughly reviewed. The mechanism of microbial growth and enrichment by conductive materials is discussed, as well as the subsequent effect on waste metabolism, methane production, syntrophic relationships and interspecies electron transfer. The porous structure, specific surface area and conductivity of conductive materials play vital roles in the facilitation of syntrophic relationships between fermentative bacteria and methanogenic archaea. In addition, the mediation of direct interspecies electron transfer (DIET) by conductive materials increases the methane content of biogas from 16% to 60% as compared to indirect interspecies electron transfer (IIET) in conventional anaerobic digestion systems. This review identifies research gaps in the field of material-amended anaerobic systems, suggesting future research directions including investigations into combined chemical-biological treatments for landfill leachate, microbial management using conductive materials for efficient pollutant removal and the capacity for material reuse. Moreover, findings of this review provide a reference for the efficient and large-scale treatment of landfill leachate by anaerobic digestion with conductive materials. Graphical abstract: Image 1 Highlights: Challenges in anaerobic digestion of landfill leachate are reviewed. Types of conductive materials are discussed for improvement of anaerobic digestion. Conductive materials enhance electron transfer and syntropy among anaerobes. Prospective on conductive materials for landfill leachate treatment are stressed.